A Novel Approach to Optimize the Design of Parts for Additive Manufacturing - Silva, F.J.G. (2020)
Additive Manufacturing (AM) is a term used to group the different manufacturing processes that use various techniques, each of which is capable of producing parts made from a wide variety of materials, such as polymers, ceramics, metals, wood, among others. All these technologies allow parts manufacturing by adding successive layers of material which can be liquid, powder or wire. In order to take advantages of the geometric freedom offered by AM, Topological Optimization (TO) is usually used. TO provides the optimal distribution of material for a given request. The main objective is weight reduction, without compromising the original resistance of an existing part produced by traditional processes. Taking advantage of the freedom allowed by the AM process and conciliating it with the CAE features, which allow to simulate the parts behavior when subjected to the expected loads, a new approach methodology was drawn in order to shorten the time needed to optimize parts design for AM. A case study was developed in order to validate the methodology established. The combination of AM and TO revealed promising results, attending to the component efficiency achieved.